Can Q-balls describe cosmological and galactic dark matter? - Susobhan Mandal; S. Shankaranarayanan (European Physical Journal C: Particles and Fields, 2025)
Abstract The Cold Dark Matter (CDM) hypothesis accurately predicts large-scale structure formation and fits the Cosmic Microwave Background temperature fluctuations (CMB). However, observations of the inner regions of dark matter halos and dwarf galaxy satellites have consistently posed challenges to CDM. On the other hand, the Modified Newtonian Dynamics (MOND) hypothesis can explain galactic phenomena but fails to account for the complex shape of the CMB and matter power spectra. CDM and MOND are effective in nearly mutually exclusive regimes, prompting the question: is there a physical mechanism where CDM and MOND share a common origin? Q-balls, which are localized, non-topological solitons, can be a bridge between the two hypotheses. Q-balls formed in the early Universe can mimic CDM at cosmological scales. Interestingly, Q-balls can exhibit MOND-like behavior in the late Universe at galactic scales, providing a unified framework. Specifically, we demonstrate that millicharged composite Q-balls formed from complex scalar fields, decoupled from the background radiation, can naturally arise during the radiation-dominated epoch. From the matter-radiation equality, we also obtain the mass of Q-balls to be 1 eV, which are much smaller than the electron mass. Using the constraints from the invisible decay mode of ortho-positronium, we obtain $$Q < 3.4 × 10^{-5}$$ Q < 3.4 × 10 - 5 . We also establish an upper bound on the number density of Q-balls, which depends on the charge of the Q-ball and the small initial charge asymmetry. Furthermore, we demonstrate that the MOND naturally emerges at the galactic scale within the framework of our Q-ball model.